Análisis de las metodologías PETI para las instituciones públicas del Ecuador (Tema Central) - Acosta, Ángel (2023)
The objective of this study is to identify the most appropriate standard for the Strategic Planning of Information Technology (PETI, as per its Spanish acronym) by studying the ICT units in charge of coordinating and controlling the creation and implementation thereof in accordance with the Institutional Strategic Plan to comply with the National Plan of Electronic Government and the government policies and objectives starting from a review of the processes of the General Coordination of Technologies of Information of the Ministry of Foreign Affairs and Human Mobility. The methodology used was a descriptive, quantitative and analytical analysis based on a survey as main source; a documentary analysis of best practices in the region and review of secondary sources for available standards for planning of information technology. The results showed that the most appropriate technical standard for the creation of PETI for the institution under study is model IT4+, as it aligns with the strategic objectives and mission objectives of the entity.